Effects of Renal Sympathetic Denervation on 24-hour Blood Pressure Variability - Zuern, Christine S.; Rizas, Konstantinos D.; Eick, Christian; Stoleriu, Cosmina; Bunk, Lena; Barthel, Petra; Balletshofer, Bernd; Gawaz, Meinrad; Bauer, Axel (Frontiers in Physiology, 2012)
Background: In patients with arterial hypertension, increased blood pressure (BP) variability contributes to end organ damage independently from mean levels of arterial BP. Increased BP variability has been linked to alterations in autonomic function including sympathetic overdrive. We hypothesized that catheter-based renal sympathetic denervation (RDN) confers beneficial effects on BPV. Methods and Results: Eleven consecutive patients with therapy-refractory arterial hypertension (age 68.9±7.0 years; baseline systolic BP 189±23mmHg despite medication with 5.6±2.1 antihypertensive drugs) underwent bilateral RDN. Twenty-four hour ambulatory blood pressure monitoring (ABPM) was performed before RDN and six months thereafter. BPV was primarily assessed by means of standard deviation of 24-hour systolic arterial blood pressures (SDsys). Secondary measures of BPV were maximum systolic blood pressure (MAXsys) and maximum difference between two consecutive readings of systolic BP (deltamaxsys) over 24 hours. Six months after RDN, SDsys, MAXsys and deltamaxsys were significantly reduced from 16.9±4.6mmHg to 13.5±2.5mmHg (p=0.003), from 190±22mmHg to 172±20mmHg (p<0.001) and from 40±15mmHg to 28±7mmHg (p=0.006), respectively, without changes in concomitant antihypertensive therapy. Reductions of SDsys, MAXsys and deltamaxsys were observed in 10/11 (90.9%), 11/11 (100%) and 9/11 (81.8%) patients, respectively. Although we noted a significant reduction of systolic office blood pressure by 30.4±27.7mmHg (p=0.007), there was only a trend in reduction of average systolic BP assessed from ABPM (149±19mmHg to 142±18mmHg; p=0.086). Conclusions: In patients with therapy-refractory arterial hypertension, RDN leads to significant reductions of BP variability. Effects of RDN on BPV over 24 hours were more pronounced than on average levels of BP.